2014
DOI: 10.1073/pnas.1418503111
|View full text |Cite
|
Sign up to set email alerts
|

The vertical occipital fasciculus: A century of controversy resolved by in vivo measurements

Abstract: The vertical occipital fasciculus (VOF) is the only major fiber bundle connecting dorsolateral and ventrolateral visual cortex. Only a handful of studies have examined the anatomy of the VOF or its role in cognition in the living human brain. Here, we trace the contentious history of the VOF, beginning with its original discovery in monkey by Wernicke (1881) and in human by Obersteiner (1888), to its disappearance from the literature, and recent reemergence a century later. We introduce an algorithm to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
287
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 244 publications
(312 citation statements)
references
References 62 publications
24
287
0
1
Order By: Relevance
“…Its role would be potentially important when the letter strings are not presented in a familiar format and would therefore be in charge of the difficult analysis of multiple visual elements (Cohen, Dehaene, Vinckier, Jobert, & Montavont, 2008) before their processing can be relayed by the left vOT cortex (see also , for a more detailed account of the role of the superior parietal lobules in reading and its connections with the left vOT area). In line with this idea, Yeatman et al (2014) reported the existence of a white matter tract that connects the vOT to the intra parietal sulcus.…”
Section: Reading Subskills: Auditory Phonology and Visual Attention Spanmentioning
confidence: 72%
“…Its role would be potentially important when the letter strings are not presented in a familiar format and would therefore be in charge of the difficult analysis of multiple visual elements (Cohen, Dehaene, Vinckier, Jobert, & Montavont, 2008) before their processing can be relayed by the left vOT cortex (see also , for a more detailed account of the role of the superior parietal lobules in reading and its connections with the left vOT area). In line with this idea, Yeatman et al (2014) reported the existence of a white matter tract that connects the vOT to the intra parietal sulcus.…”
Section: Reading Subskills: Auditory Phonology and Visual Attention Spanmentioning
confidence: 72%
“…It connects dorsolateral and ventrolateral visual cortex. 42,43 Dorsal extra-striate visual areas are specialized for analyzing spatial aspects of object features and processing motion-related information, while ventral regions of the occipital and temporal lobes are specialized for form perception and object recognition. 61,62 Our findings suggest that the communication between the two streams may be affected in strabismic amblyopia.…”
Section: Discussionmentioning
confidence: 99%
“…42 The first step is to generate a whole-brain connectome by probabilistic tractography. Probabilistic tractography assumes a distribution of principal direction of orientations instead of a single orientation, thus it performs better at locations where complicated fiber crossings are present.…”
Section: White Matter Tract Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the changes in cross-striated muscle during contraction were known in the 19th century but forgotten, only to be rediscovered in the mid-20th century (20). The vertical optical fasciculus was described by the neuroanatomist Wernicke in 1881 but later disputed and forgotten until the recent work of Wandell and colleagues (21). Moreover, scientists who are concerned with only the facts and not the process miss out on the rich human drama of perseverance, serendipity, inventiveness, and conflict that characterizes the history of science.…”
mentioning
confidence: 99%